Phosphogypsum and poultry manure enhance diversity of soil fauna, soil fertility, and barley (Hordeum aestivum L.) grown in calcareous soils - Esawy Mahmoud; Adel M. Ghoneim; Mostafa Seleem; Raghda Zuhair; Ahmed El-Refaey; Naglaa Khalafallah (Scientific Reports, 2023)
Abstract Enrichment of calcareous soils with phosphogypsum and poultry manure amendments could increase nutrient availability, improve calcareous chemical characteristics, and enhance barley plant growth. In the current study, phosphogypsum (PG) and poultry manure (PM) were used to determine the effects of PG and PM application on soil fauna diversity, soil fertility, and barley yield. The pot experiment treatments were: C: control; PG1: 4.20 g kg−1 soil; PG2: 6.30 g kg−1 soil; PM1: 4.20 g kg−1 soil; PM: 6.30 g kg−1 soil, and their combinations. The results indicated that the application of PM alone or combined with PG had significant effects on the microbial biomass carbon (MBC), organic matter (OM), soil NPK availability, and yield of barley. Collembola and Prostigmata accounted for 50.0 and 43.3%, respectively, of the total number of soil fauna. Shannon and evenness indices increased significantly in the soil amended with PM alone or combined with PG. Amended soil with PG and/or PM significantly increased the yield and yield components of plants compared to the control. The PM1PG2 treatment increased the yield by 76.2% above the control.